The influence of green advertising on sustainable plastic packaging waste disposal: case of Beitbridge urban households. - Chibungu, Robert (Midlands State University, 2019)
As a consequence of diverse human activities such as plastic littering, the planet has suffered rampant pollution resulting in the global outcry for the reduction of carbon footprints by individuals and organisations through engaging in eco-friendly activities (World Bank, 2018). Thus, the present study was meant to examine the influence of green advertising on sustainable plastic packaging waste disposal. A Case of Beitbridge urban households. To this end the researcher incorporated green advertising variables in the conceptual framework to construct four (4) objectives to guide the research which are (1) determining the influence of emotional appeals on household recycling intention (2) examining the influence of moral appeals on recycling intention (3) ascertain the relationship between household attitude towards waste disposal and recycling intention and lastly (4) determining the effect of recycling intention on recycling behaviour. Relevant literature from various scholars on the influence of green advertising and sustainable waste disposal was scrutinized. Both theoretical and empirical literature perspectives were taken into account to identify the major ideas and concepts related to waste disposal and green advertising. Though scholars unanimously agree that waste is a huge threat to life on the planet, the major areas of argument emerged on the level of practice of proper waste disposal between developed and less developed nations. A pragmatism philosophy which incorporated both the quantitative and qualitative methods where data was collected from 377 respondents comprising households, representatives from environmental agencies and institutions responsible for garbage management in Beitbridge was adopted. A structured questionnaire based on a 5-point Likert scale was used to gather data and this was complimented with confirmatory interviews conducted through purposive sampling. Research findings show that there is a positive relationship between household attitudes, green emotional and moral appeals to recycling behaviour mediated by recycling intention. The deductions made from the findings denote the need for intensive education campaigns to close the information gap about the detrimental effects of plastic litter on the environment. Recycling facilities also need to be availed to make the recycling task feasible. The study recommends that more resources are committed to changing household attitudes so that they become more positively inclined to protecting the environment which would induce the desire to recycle for planet sustenance.